2006
DOI: 10.1091/mbc.e06-05-0377
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Fission Protein hFis1 Requires the Endoplasmic Reticulum Gateway to Induce Apoptosis

Abstract: Mitochondrial fission ensures organelle inheritance during cell division and participates in apoptosis. The fission protein hFis1 triggers caspase-dependent cell death, by causing the release of cytochrome c from mitochondria. Here we show that mitochondrial fission induced by hFis1 is genetically distinct from apoptosis. In cells lacking the multidomain proapoptotic Bcl-2 family members Bax and Bak (DKO), hFis1 caused mitochondrial fragmentation but not organelle dysfunction and apoptosis. Similarly, a mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
95
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 53 publications
11
95
0
1
Order By: Relevance
“…In this work, it was demonstrated that expression of fission dead Fis1 could still induce cell death. When the apoptotic dead mutant of Fis1 was expressed, mitochondria could still undergo fission but there is no induction of cell death [73]. Overall, these results show that although fission is required for cell death, fission in itself was not sufficient for cell death induction.…”
Section: What Is the Role Of Mitochondrial Fission In Cell Death?mentioning
confidence: 83%
“…In this work, it was demonstrated that expression of fission dead Fis1 could still induce cell death. When the apoptotic dead mutant of Fis1 was expressed, mitochondria could still undergo fission but there is no induction of cell death [73]. Overall, these results show that although fission is required for cell death, fission in itself was not sufficient for cell death induction.…”
Section: What Is the Role Of Mitochondrial Fission In Cell Death?mentioning
confidence: 83%
“…Overexpression of the mitochondrial fission protein Fis-1 induces apoptosis in some cell types, which suggests that mitochondrial fission may be a driver of apoptosis (Alirol et al, 2006;James et al, 2003;Yu et al, 2005).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Concomitantly, Drp1 and hFis1 levels are elevated in early apoptosis in cultured cardiomyocytes (Parra et al, 2008;Ong et al, 2010) and in heart failure model as well (Chen et al, 2009). Drp1 (Frank et al, 2001;Lee et al, 2004) and hFis1 (Lee et al, 2004;Alirol et al, 2006) participate in the process of cell death. During cardiac myocytes apoptosis, Drp1 translocates to mitochondria from cytosol (Wang et al, 2011a).…”
Section: Mitochondria Mediate Apoptosis In Heartmentioning
confidence: 99%